Practicality of Android-Based Mobile Learning for Teaching Remo Putri Gaya Tawi Dance in Vocational Schools - Nurul, Ainin; Cao Jia; Reno Wulan; Setyo Yanuartuti; Retnayu Presetyanti; Welly Suryandoko (Universitas Nahdatul Ulama Surabaya, 2025)
This study aims to examine the practicality of Android-based mobile learning developed for teaching the Remo Putri Gaya Tawi dance in dance arts subjects at vocational schools in the digital era. This research employed a case study approach within a research and development framework using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. Data were collected through observations of learning implementation, teacher and student response questionnaires, and expert judgment instruments assessing learning implementation, learning videos, and assessment sheets. The results of the learning implementation observations showed that the Android-based mobile learning achieved an average score of 80%, indicating a practical category as it met the implementation criterion of ≥75%. Teachers provided positive responses regarding readability, clarity of material, video quality, and alignment with students’ learning needs. Students also reported that the application was easy to use, engaging, and effective in helping them understand and practice the movements of the Remo Putri Gaya Tawi dance independently and collaboratively. Furthermore, expert judgment results indicated a high level of practicality, with scores of 97.6% for learning implementation, 80% for learning video practicality, and 98.45% for the practicality of assessment sheets. These findings suggest that Android-based mobile learning integrated with project based learning model is practical and feasible for supporting dance learning in vocational schools while enhancing student engagement and learning autonomy.